2019
DOI: 10.1111/geb.13029
|View full text |Cite
|
Sign up to set email alerts
|

Species niches, not traits, determine abundance and occupancy patterns: A multi‐site synthesis

Abstract: HAL is a multidisciplinary open access archive for the deposit and dissemination of scientific research documents, whether they are published or not. The documents may come from teaching and research institutions in France or abroad, or from public or private research centers. L'archive ouverte pluridisciplinaire HAL, est destinée au dépôt et à la diffusion de documents scientifiques de niveau recherche, publiés ou non, émanant des établissements d'enseignement et de recherche français ou étrangers, des labora… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
22
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(27 citation statements)
references
References 55 publications
5
22
0
Order By: Relevance
“…We found contrasting AORs for native and alien woody species, providing evidence that widespread native species are usually locally abundant, whereas widespread alien species may be either locally abundant or rare. Our results for native species in an island setting are consistent with previous studies on plants from temperate and tropical regions (Blackburn et al, 2006;Arellano & Macía, 2014;Díaz et al, 2020;Marino et al, 2020), which are largely drawn from continental contexts (but see Buckley & Freckleton, 2010). The decoupled relationship between abundance and occupancy that we observed for alien woody species, however, appears to be an exception to the general rule that AORs are positive, even for alien species (Holt & Gaston, 2003;Buckley & Freckleton, 2010;Rigal et al, 2013;Sarabeev et al, 2018;Miranda & Killgore, 2019).…”
Section: Contrasting Abundance-occupancy Relationshipssupporting
confidence: 91%
“…We found contrasting AORs for native and alien woody species, providing evidence that widespread native species are usually locally abundant, whereas widespread alien species may be either locally abundant or rare. Our results for native species in an island setting are consistent with previous studies on plants from temperate and tropical regions (Blackburn et al, 2006;Arellano & Macía, 2014;Díaz et al, 2020;Marino et al, 2020), which are largely drawn from continental contexts (but see Buckley & Freckleton, 2010). The decoupled relationship between abundance and occupancy that we observed for alien woody species, however, appears to be an exception to the general rule that AORs are positive, even for alien species (Holt & Gaston, 2003;Buckley & Freckleton, 2010;Rigal et al, 2013;Sarabeev et al, 2018;Miranda & Killgore, 2019).…”
Section: Contrasting Abundance-occupancy Relationshipssupporting
confidence: 91%
“…So far, the majority of studies have focused on single traits rather than on trait combinations or trait syndromes (but see Díaz et al, 2016; Guo et al, 2018) as predictors of large and local distribution patterns. However, no single trait can completely describe a species’ ecological strategy (Winemiller et al, 2015; Marino et al, 2020). Rather, species’ local abundance and broad‐scale distribution patterns might be affected by different sets of traits (Marino et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…However, no single trait can completely describe a species’ ecological strategy (Winemiller et al, 2015; Marino et al, 2020). Rather, species’ local abundance and broad‐scale distribution patterns might be affected by different sets of traits (Marino et al, 2020). It has been suggested that locally rare and geographically restricted plant species differ systematically from more common species in functional traits that are related to species’ productivity, competitive ability, dispersal, regeneration and persistence (Murray et al, 2002).…”
Section: Introductionmentioning
confidence: 99%
“…Even though flooding is the most important environmental characteristic driving species distribution in the plot, the fundamental niche of the three Myrcia species potentially encompasses a much wider variation of conditions than the environments of the study site, as the species occur in different vegetation types and are not restricted to areas subject to flooding at the geographic scale (Appendix ). Thus, in the white‐sand forest studied, the species can use the most common environmental condition (niche position, Marino et al., 2019) and patches subject to flooding may work as areas of refuge from strong competitors and/or natural enemies (Baraloto et al., 2007), which drives the species’ realized niche. The same reasoning may apply to other species in the community, because most occur in both flooded and dry patches within the study plot (Appendix ).…”
Section: Discussionmentioning
confidence: 99%